Impact of Social Media On Consumer Purchase Behaviour During COVID-19 Pandemic - Kah Boon Lim; Sook Fern Yeo; Cheng Ling Tan; Wong Wei Wen (International Journal of Entrepreneurship, Business, and Creative Economy, 2022)
Social media has been used by people to create and share content with the public. Consumers have changed their purchasing habits from offline to online purchases during the COVID-19 pandemic. Social media is also changing sellers' and buyers' specialised strategies. This study aimed to study the factors influencing consumer purchasing behaviour via social media during the COVID-19 outbreak. 215 young adults from three Malaysian states which are Johor, Melaka, and Selangor, have been invited to participate in this study by answering a set of questionnaires. The successful response rate is 93.02%, where 200 completed questionnaires were used for data analysis in this study. The four independent variables, price, convenience, product variety, and risk, are tested in relation to the dependent variable, consumer purchase behaviour during the COVID-19 outbreak. The measurement items of all the four independent variables and dependent variables were adopted from the past research studies. The collected data were entered into SPSS version 26 and then tested using Partial Least Square Structural Equation Modelling (PLS-SEM 3.3.3). All hypotheses were found to be supported by the analysis results. Lastly, the findings of this study will help marketers understand consumer purchasing behaviour via social media during the COVID-19 pandemic.